Efficacy of intravenous delta-aminolaevulinic acid photodynamic therapy on rabbit papillomas. - Lofgren, L. A. (1995)
Endogenously induced protoporphyrin IX (PPIX), a metabolite of delta-aminolaevulinic acid (ALA), has been evaluated as a photosensitising agent for destruction of papillomas in cottontail rabbit papillomavirus-infected Dutch belted and New Zealand rabbits. Three factors were evaluated: (1) relative retention ratio of drug in normal tissue, papilloma and plasma over time; (2) tissue tolerance to treatment factors; and (3) efficacy of treatment protocol. Three drug doses of ALA were examined: 50, 100 and 200 mg kg-1. Actual PPIX concentrations in tissue and plasma were determined spectrophotofluorometrically. The optimal treatment time occurred 3-6 h post ALA injection. The highest PPIX concentration ratio between papilloma and normal skin was 6:1. Different light doses were investigated, using an injection to exposure interval of 3 h and an irradiance of 100 mW cm-2 at a wavelength of 630 nm. Efficacy without risk of significant damage to normal skin was obtained using 100-200 mg kg-1 ALA and 40-60 J cm-2. A long-term (3 months) cure rate of 82% was obtained with a single treatment, provided that papilloma depth did not exceed 8 mm, volume was not more than 1000 mm3 and the plasma concentration of PPIX immediately before exposure was above 500 micrograms ml-1. The short time between injection and treatment and high efficacy, together with PPIX disappearance from plasma and tissue within 24 h, make injected ALA a highly attractive drug for photodynamic therapy.